BUSINESS DEVELOPMENT PROGRAM OPTIMIZATION - B. Gusakov; A. Sotnikova (Вестник университета)
The objective function of optimization is to choose the option that provides the max-imum growth rate of assets and the minimum period of the program with limited initial invest-ment resources. The number of options is reducing when assigning the main priorities to the ob-jects of the program - technological priority, a small payback period and an additional priority of communication. The communication priority is taking into account when two or more objects need to be launching simultaneously. A method of optimizing the business development program, which requires the formation of several development options by rearranging the sequence of ac-tivities, included in the basic program, has been proposed in the article. As an indicator of the ef-fectiveness and optimality of the program, it has been proposed to use the coefficient of innovation management, which characterizes the average growth rate of assets involved in the implementation of the program. The optimal program has been considered on the example of a trade organization.